Analysis of PT XYZ Mask Business Development Strategy during the COVID-19 Pandemic - Veronica Halim; Hanssen Hanssen; Scherly Hansopaheluwakan; Wendy Junaidi (Journal of Business, Management, & Accounting, 2022)
PT.XYZ is a household electronic product marketing company that diversifies into medical device products, one of which is a medical mask product which is the object of this research. The purpose of this research is to analyse production challenges, marketing strategies, and marketing challenges. The research method used is descriptive qualitative with interview techniques to 5 PT.XYZ employees and 3 PT.XYZ mask users, which are processed using SWOT Analysis, STP, and Marketing Mix. The results of this study stated that PT. XYZ focuses on digital marketing to be able to increase brand awareness of its medical mask products, but the results of this study state that digital marketing is not effective and Word of Mouth is found to be effective in building company brand awareness.